Farewell to Political Obligation: In Defense of a Permissive Conception of Legitimacy. (3rd November 2015) - Zhu, Jiafeng
Abstract: In the recent debate on political legitimacy, we have seen the emergence of a revisionist camp, advocating the idea of 'legitimacy without political obligation, ' as opposed to the traditional view that political obligation is necessary for state legitimacy. The revisionist idea of legitimacy is appealing because if it stands, the widespread skepticism about the existence of political obligation will not lead us to conclude that the state is illegitimate. Unfortunately, existing conceptions of 'legitimacy without political obligation' are subject to serious objections. In this article, I propose a new conception of 'legitimacy without political obligation, ' and defend it against various objections that the revisionist idea of legitimacy is either conceptually or morally mistaken. This new conception of legitimacy promises to advance the debates between anarchists and statists by making the task of philosophical anarchists significantly more difficult.